Analysis of the Feasibility of Investment in Damai Permai Housing in Tangerang Regency - Tuti Rahmawati; Ida Ayu Ari Angreni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Housing is one option that is intended to satisfy the community's housing requirements. This provides business opportunities for developers to build residential property as a fulfillment of community needs. Housing projects must be based on a fairly in-depth evaluation of investment feasibility. In this study, the housing project under study was the Damai Permai housing project built in Tangerang Regency. This study aim to determine the financial feasibility of an investment proposal for the development of Damai Permai Housing in the Tangerang Regency of Indonesia. This study uses a Net Present Value (NPV) value approach, Benefit Cost Ratio (BCR), Break Event Point (BEP), and Payback Period (PP). Based on these values it will be known whether the Damai Permai housing project in Tangerang Regency is feasible or not and how long the payback period is.